Implementasi Program Madrasah Habituasi sebagai Upaya Membentuk Karakter Siswa - Al-Ghozali, M. Dzikrul Hakim; Sa'adah, Dewi Mambaus; Hakim, Denny Nuril (YASIN, 2025)
The research aims to analyze the effectiveness of habituation programs in shaping religious characters and disciplines of students at MAN 6 Jombang. The study uses a qualitative descriptive approach with data collection techniques through observation, interviews and documentation. The habituation program at MAN 6 Jombang proved to have a positive impact on discipline, responsibility, and customs of student worship. Students who initially have difficulty adjusting to this program gradually begin to get used to it and carry it out with consciousness. In addition, the program strengthens togetherness between students through Friday Culture and Friday Healthy activities. Despite challenges, such as difficulty in building discipline and lack of support from the family environment, various strategies such as teacher mentoring, the active role of the student council, and the implementation of educational sanctions proved effective in improving student participation. The habituation program at MAN 6 Jombang has been successful in shaping religious characters and student disciplines. Sustainability and innovative development in this program, such as the provision of healthy food stands and literacy integration, are expected to further improve its effectiveness. With support from various parties, the program has great potential to continue to positively impact students in madrasa and in their daily lives.